2016
DOI: 10.1186/s12879-016-1883-6
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional education program at substance dependence treatment centers improves patient knowledge and hepatitis C care

Abstract: Background: HCV treatment among people who inject drugs (PWID) is low. Education programs may be suitable strategies to improve patients' knowledge about their condition and to overcome barriers to access treatment. Methods: The Health Educational Program (HEP) consisted of patient workshops and educational videos and leaflets, and healthcare professionals' workshops. HEP was implemented at seven substance dependence treatment centers (STDC) in Portugal. The study comprised two cross-sectional evaluations cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Low engagement may be addressed by education programs: for patients, options include brief group sessions at drug treatment services including workshops, Q&A sessions, leaflets, videos on the basics of HCV and risk behaviors for transmission, HCV treatment pathway, right of equal access,16,17 and interactive digital health decision aids 18. Education sessions for health care professionals (HCPs) directed in primary care19 and drug treatment services,17 and HCV awareness campaigns directed to the general public may be of benefit. Programs that actively seek patients such as pop-up and short-term services delivered by clinics in neighborhoods with high HCV prevalence are effective in promoting treatment engagement 20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low engagement may be addressed by education programs: for patients, options include brief group sessions at drug treatment services including workshops, Q&A sessions, leaflets, videos on the basics of HCV and risk behaviors for transmission, HCV treatment pathway, right of equal access,16,17 and interactive digital health decision aids 18. Education sessions for health care professionals (HCPs) directed in primary care19 and drug treatment services,17 and HCV awareness campaigns directed to the general public may be of benefit. Programs that actively seek patients such as pop-up and short-term services delivered by clinics in neighborhoods with high HCV prevalence are effective in promoting treatment engagement 20…”
Section: Resultsmentioning
confidence: 99%
“…A tailored approach with different options for engagement is most likely to be successful 40. Referral processes can be facilitated by education for HCP at drug treatment services17 and primary care;19 support from peer mentors facilitates linkage to start HCV treatment 41…”
Section: Resultsmentioning
confidence: 99%
“…Health education programmes can be successfully conducted only when they are preceded by reliable and thorough analyses of the target group’s knowledge level. An analysis of papers available in the literature on the knowledge level of HCV among different groups reveals that the majority of studies are carried out using proprietary questionnaires, which makes comparison of the study results impossible [ 15 20 ]. A vast majority of the tools is not validated: their authors do not quote indices of repeatability or measurement reliability, which may challenge the validity of the knowledge level measurement in the studied groups.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of HCV-related prevention and care services among PWID, a traditionally difficult to reach population, has historically been limited due to a range of barriers operating at the patient, service provider, and system level [Paterson, Hirsch, Andres, 2013;Bruggmann, Grebely, 2015;Bruggmann, 2012]. Education of both patients and providers may help to address barriers preventing HCV care [Bruggmann, 2012;Marinho et al, 2016]. Research has suggested that adequate knowledge regarding HCV treatment may be an integral precursor to increased engagement with HCV-related care and treatment uptake [Marinho et al, 2016;Treloar et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Education of both patients and providers may help to address barriers preventing HCV care [Bruggmann, 2012;Marinho et al, 2016]. Research has suggested that adequate knowledge regarding HCV treatment may be an integral precursor to increased engagement with HCV-related care and treatment uptake [Marinho et al, 2016;Treloar et al, 2011]. In spite of this, data reporting the extent to which PWID are cognisant of the latest developments in HCV treatment, particularly their high cure rates, are scarce.…”
Section: Introductionmentioning
confidence: 99%